2021
DOI: 10.3390/app11072887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beauveria bassiana-Seed Treatment on Zea mays L. Response against Spodoptera frugiperda

Abstract: Spodoptera frugiperda is a widely distributed insect pest that causes major economic losses in various crops, particularly maize. On the other hand, Beauveria bassiana is an entomopathogenic fungus that establishes symbiotic associations with many plants and contributes to tolerance against biotic and abiotic stresses. In the present work, in laboratory experiments, the effects of the B. bassiana strain GHA, in addition to a native strain (PTG4), delivered via seed treatment in maize seedlings, were evaluated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In contrary, Gao et al ( 2021 ) found that the exposed 3rd instar larvae of S. frugiperda to sub-lethal concentrations of spinetoram had no effects on the emergence rate of adults. Nevertheless, feeding of the 3rd to 6th instars larvae of S. frugiperda on maize seedlings inoculated with B. bassiana (1 × 10 6 spores mL −1 ) reproduced fewer adult male moths compared to the control treatment (Kuzhuppillymyal-Prabhakarankutty et al 2021 ). We also observed no significant changes in the adult longevities of both instar larvae treated with the selected insecticides and their control treatments.…”
Section: Discussionmentioning
confidence: 98%
“…In contrary, Gao et al ( 2021 ) found that the exposed 3rd instar larvae of S. frugiperda to sub-lethal concentrations of spinetoram had no effects on the emergence rate of adults. Nevertheless, feeding of the 3rd to 6th instars larvae of S. frugiperda on maize seedlings inoculated with B. bassiana (1 × 10 6 spores mL −1 ) reproduced fewer adult male moths compared to the control treatment (Kuzhuppillymyal-Prabhakarankutty et al 2021 ). We also observed no significant changes in the adult longevities of both instar larvae treated with the selected insecticides and their control treatments.…”
Section: Discussionmentioning
confidence: 98%
“…The isolate B. bassiana GHA has been developed into several commercially available biopesticide products (BotaniGard ® ES and Mycotrol ® ) (BioWorks, Inc., New York, NY, USA) in several countries, including Australia, Canada, and the US [ 46 , 47 , 60 ]. The isolate is able to control a diversity of invertebrate pests, including DBM [ 48 ], Colorado potato beetle [ 61 ], emerald ash borer [ 62 ], tobacco whitefly [ 63 ], plant bugs [ 64 ], coffee borer beetle [ 65 ], house fly [ 66 ], western cherry fruit fly [ 67 ], and fall armyworm [ 68 ]. Testing isolates CTL20 and I12 Damo against other insect pests is required to assess their host range and examine their consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Some protect host plants from stress and promote their growth [ 3 , 4 ]. In addition to Beauveria bassiana ’s potential as an entomopathogen, this fungus establishes as an endophyte, after being naturally implanted in plant tissues or artificially applied, which protects from herbivores [ 5 , 6 , 7 ], pathogens [ 8 , 9 ], or abiotic stress, among others [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%